2019
DOI: 10.29245/2689-999x/2019/4.1157
|View full text |Cite
|
Sign up to set email alerts
|

Ventilator-Associated Pneumonia and In-Hospital Mortality: Which Risk Factors may predict In-Hospital Mortality in Such Patients?

Abstract: Background: Ventilator-associated pneumonia (VAP) remains a common case of intensive care unite (İCU) and hospital morbidity and mortality despite advances in diagnostic techniques and manegment. One of most important point for such patients is identification of predictors for mortality in term for futher their modification and reduction of mortality rate.Objective: We aimed to determine the most important risk factors for short-term mortality in patients with VAP in mechanically ventilated patients Methods: T… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
8
0
1

Year Published

2021
2021
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(10 citation statements)
references
References 15 publications
1
8
0
1
Order By: Relevance
“…58 Meanwhile, Sadigov et al reported that the only independent risk factor for increased hospital mortality in VAP patients was A. baumannii infection. 40 However, in previous studies, length of hospital stays more than 9 days preceding the incidence of nosocomial pneumonia was a significant predictor of mortality. 38,59 Prolonged hospitalization was linked to higher risk of infection with antibiotic resistant pathogens, which resulted in higher mortality.…”
mentioning
confidence: 85%
See 1 more Smart Citation
“…58 Meanwhile, Sadigov et al reported that the only independent risk factor for increased hospital mortality in VAP patients was A. baumannii infection. 40 However, in previous studies, length of hospital stays more than 9 days preceding the incidence of nosocomial pneumonia was a significant predictor of mortality. 38,59 Prolonged hospitalization was linked to higher risk of infection with antibiotic resistant pathogens, which resulted in higher mortality.…”
mentioning
confidence: 85%
“…36,37 Meanwhile, Chen et al, Kumari et al, and Sadigov et al reported that A. baumannii was the most prevalent CR-GNB pathogen, accounting for 78.7%, 37.4%, and 37.1%, respectively. [38][39][40] This variation could be the result of geographical differences between the countries, patient population and clinical setting. 20 Determination of whether the gram-negative isolate is a carbapenemase producer is essential for epidemiological studies and also for selection of the appropriate treatment for infections.…”
mentioning
confidence: 99%
“…11. Aspiration of subglottic secretion-continuous 2 , by suction tubing for evac aspiration 3 , suction force: 100-150 mmHg (Figures 5 and 6).…”
Section: Deep Vein Thrombosis Prophylaxismentioning
confidence: 99%
“…Ventilator-associated pneumonia (VAP) in the intensive care unit (ICU) is a complex and multifactorial clinical condition connected with high morbidity (4-61%) and mortality (40-43%) as well as considerable treatment costs [1][2][3][4]. The length of stay of a patient with VAP in the ward usually fluctuates between 10 and 21 days.…”
Section: Introductionmentioning
confidence: 99%
“…Mechanically ventilated patients are unable to clear oropharyngeal secretions; therefore, they are at increased risk for bronchopulmonary aspiration and respiratory infections (18) . VAP is one of the consequences of bronchopulmonary aspiration and results in high in-hospital mortality rates (35)(36) . The VAP prevention bundle, which includes (i) elevated position at 30 and 45°, (ii) daily interruption of sedation and daily assessment of extubation conditions, (iv) peptic ulcer prophylaxis (stress ulcer) and (v) deep vein thrombosis prophylaxis (unless contraindicated) (37) , being an important strategy that, when used efficiently, positively impacts patient outcomes and quality of care (25) , because it allows nurses and other healthcare professionals to provide the best possible care, supported by evidence-based research and practices (32) .…”
Section: Explanatory Variablesmentioning
confidence: 99%